The prevalence and determinants of anterior cruciate ligament rupture among athletes practicing football in Jeddah Avenues 2020 - Fahad Salem Alqarni; Khalid Omair Alshehri; Turki Muteb Alotaibi; Assaf Nahar Alsulami; Abdulaziz Omair Alshehri; Khaled Saeed Aseri (Journal of Family Medicine and Primary Care, 2022)
Background: Anterior cruciate ligament (ACL) tear is a common sport injury and one of the most serious sport injuries affecting non-professionals and professional athletes. It is most commonly torn during sports that involve sudden stops and changes in direction such as football. Objective: To measure the prevalence and determinants of anterior cruciate ligament rupture as well as assess knowledge about it among young adult athletes practicing football. Materials and Methods: An analytical cross-sectional study based on a questionnaire was carried out during the period from December 2019 to March 2020 among a sample of Saudi athletes recruited from natural grass, artificial turf, and dirt football fields in the Jeddah region. A structured questionnaire composed of four parts was used to collect data: socio-demographic variables, questions to assess awareness and knowledge of ACL, questions to assess the prevalence and determinants of ACL, and description of cases and the Arabic version of the Lysholm Knee Score (LKS) to assess the impact of ACL injury on patients' daily life. Results: The study included 320 participants. Their age ranged between 15 and 40 years with an arithmetic mean of 27.9 and a standard deviation of ±6.8 years. The majority of them were males (97.8%). The prevalence of ACL injury was 14.7% among the participants; it was significantly higher among overweight and obese subjects (P = 0.042) as well as those who reported more than 10 training weekly hours (P = 0.034). Most of the playgrounds at the time of injury were either artificial turf (44.7%) or dirt football fields (34%). Overall, the level of adequate knowledge about ACL was observed among most of the participants (70.3%). The only factor significantly associated with the level of participants' knowledge about ACL was the level of physical activity, P = 0.011. The total of LKS ranged between 21 and 100 with a median (inter-quartile range) of 82.5 (57–91). Conclusion: The prevalence rate of ACL injury among athletes in Jeddah, Saudi Arabia, is within the world wide range. Their awareness and knowledge of ACL are encouraging, although some risk factors were not well known. The quality of life of injured athletes was high, irrespective of demographic as well as physical factors and the history of surgical repair.